JAMINAN PERLINDUNGAN HUKUM TERHADAP PEREMPUAN KORBAN TINDAK PIDANA KEKERASAN SEKSUAL - Ismail, Mahsun; Purwandi, Agustri; Subroto, Gatot; Pakendek, Adriana; Wulandari, Safitri; R., Mohammad Ilham A. (Legal Standing : Jurnal Ilmu Hukum, 2024)
Sexual violence is currently increasing in terms of number or modus operandi committed by the perpetrator, based on the National Commission on Violence Against Women (Komnas Perempuan) in 2023 the crime of sexual violence reached 7,858 cases. The increase in sexual violence is triggered by various factors, both from family factors, the environment, and social media which are increasingly massive cornering the position of women as vulnerable to sexual violence. The method used in empirical research using a victimology approach. The results of this study show that the legal protection mechanism carried out by investigators of the PPA unit of Pamekasan Police against victims of sexual violence continues to prioritize and accommodate the legal interests of victims by cooperating with parties concerned with the protection and recovery of victims' conditions. Second, the form of legal protection carried out by providing complete information on the rights of victims both in terms of rehabilitation and recovery services, or access to legal assistance at the examination level. As well as conducting trauma healing in cases of sexual violence with the aim of a mental, emotional, and physical recovery process that aims to help victims recover from the traumatic impact caused by the experience of sexual violence.